Penerapan Budaya Organisasi terhadap Peningkatan Kinerja Karyawan pada CV. Desain & Bangunan Sukabumi - Munandar, Wita Aulia; Samsudin, Acep; Komariah, Kokom (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2020)
In an industrial world, organizational culture is an important element that must be highlighted in an industry because it can affect the performance of its employees. A company will have more advantages if its employees are able to work well in accordance with their main duties and functions, it can be dealt with by growing a good culture in order to provide examples of good ways of working for fellow employees. The purpose of this study is to determine how much influence the organizational culture of improving employee performance on the CV. Design & Building Sukabumi, with a population of CV employees. Sukabumi Design & Building. The population in CV. Sukabumi design & Building totaling 50 respondents, proving the results of this hypothesis using simple linear analysis, the results obtained from this study are, the results of the t test in this study amounted to 13,587 with a significant value of 0,000 significant value of 0,000 smaller than 0.05 (0,000 <0.05). From this it can be interpreted that there is a positive influence of organizational culture on employee performance in the CV. Sukabumi Design & Building.